White-tailed eagle (Haliaeetus albicilla) as the definitive host of Sarcocystis lutrae in the Czech Republic - Máca, Ondřej; González-Solís, David (Frontiers in Veterinary Science, 2022)
The white-tailed eagle, Haliaeetus albicilla, has been involved in the life cycle of several Sarcocystis species as intermediate and definitive host. To date, it is supposed that the eagle might play the role as definitive host for S. lutrae and herein we tried to elucidate it based on morphometric and molecular analyses. One out of two eagles harboured oocysts (17.0−17.4 × 11.3−11.9 µm) and sporocysts (11.3−12.3 × 8.3−9.3 µm) in the intestinal mucosa, whose sequences at 18S rRNA, 28S rRNA, ITS1 and cox1 showed similar identity (97.64−100%) to published sequences of S. lutrae from other hosts. The presence of sporulated oocysts in the lamina propria of villi confirms that S. lutrae truly infects the white-tailed eagle. The white-tailed eagle is confirmed as definitive host of S. lutrae in the Czech Republic.